Development of Mind Meister-Based Learning Media in the Basics of Electronics Engineering Subject at SMK YPM 1 Taman to Improve Learning Motivation - Nizar Sampramudya Yafie; Fendi Achmad; Meini Sondang Sumbawati; Yulia Fransisca (Journal of Educational Technology Studies and Applied Research, 2026)
A decline in student learning motivation persists, largely due to the use of outdated instructional media and teaching models that cause students to become easily bored with the material. To address this issue, the use of website-based instructional media using mind meister platform was proposed as a solution. This study implemented mind meister to assess the extent to which this tool could boost learning motivation in the "fundamentals of electronic engineering" subject. A quasi-experimental design was employed, utilizing observations, interviews, and questionnaires to gather data on student interest. The results demonstrated the practicality of the instructional media and a significant increase in learning motivation; an average score of 2.77 (or 69.19%) was achieved, placing it in the "practical" category. Furthermore, normality tests for learning motivation yielded Sig. (2-tailed) values of 0.062 and 0.111 (both > 0.05), satisfying the prerequisites for parametric statistical analysis. An independent samples t-test comparing the experimental and control groups resulted in a Sig. (2-tailed) value of 0.000 (< 0.05). Regarding effectiveness, a 4.38% difference was observed between the experimental group (using mind meister) and the control group (using PowerPoint), with the experimental group demonstrating superior levels of engagement and learning motivation. Ultimately, the use of modern instructional media helps mitigate the decline in student learning motivation.